Stan i perspektywy badań naukowych w Akademii Ekonomicznej w Poznaniu - Borowski, Stanisław (Wydział Prawa i Administracji UAM, 1976)
In 1976, the Academy of Economies in Poznań celebrated the 50th anniversary. During its half century history the School has largely developed the scope of research and university teaching. At present it is possible to distinguish eleven main groups of scientific branches in which the chool manifests its activity, namely: 1. political economy, 2. economic policy, planning and regional science, 3. sociology, 4. demography, 5. economic history, 6. economics of production and management, 7. economics of trade, 8, finance and accounting, 9. law and insurance, 10. statistics and econometrics, 11. commodity science. Within that vast range of branches the scholars at the Academy elaborated many theoretical and methodologicall problems. The centres, at which the mentioned branches of science have been cultivated, co-operate with the institutions and enterprises the activity of which are socio-economic policy, production or services respectively. We mention for instance such institutions as: Commission of Planning at the Government, Ministry of Internal Commerce;, Ministry of Finance, Ministry of Labour, Wages and Social Affaires, Central Statistical Office, Government Commission for Population, great enterprises, municipality and local governments. Within that range of scientific branches the Academy has carried on various exchange with foreign institutions. The scope of that exchange are scientific publications and editorial services; visiting professors, research students and graduates; research studies on common problems as well as symposia and conferences. In 1974 - 1976, some experts have undertaken forecasting works concerning research problems and new branches of science at the Academy till 1990. They have elaborated the following prognoses: 1. research studies on fundamental problems, 2. co-operation with the leading research institutions abroad, 3. new branches of science, 4. teaching process, 5. co-operation with institutions and enterprises, 6. economic, demographic and social consequences of the development mentioned in the foregoing points, 7. technical equipment of the Academy and its laboratories. They have i.a. accepted the principle that the results of the research studies on fundamental problems are also the main sources of the new branches of science.
Recent Results and Perspectives of the Research Work, at the Academy of Economics in Poznań